Achieving specialist status. (15th August 2015) - Robinson, Philip
Abstract : Few aspiring vets enter vet school with the intention of becoming a government vet and Philip Robinson was no different. But having worked as a clinician, a state vet and an epidemiologist, his career trajectory has led him to become the first RCVS Recognised Specialist in State Veterinary Medicine